PEMBIAYAAN SEKTOR PERTANIAN OLEH BANK SYARIAH UNTUK MENINGKATKAN NILAI TUKAR PETANI DI PROVINSI JAWA TIMUR - admin; Akhmad Sobrun Jamil (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2018)
As an intermediary institution, Islamic banking has an important role in channeling financing, especially in the agricultural sector. The financing of the agricultural sector is considered more suitable to be carried out by Islamic banks because in channeling financing does not recognize the term interest but uses a profit sharing system. The use of a profit sharing system is considered fairer because it does not burden the farmers, especially when the yields are not satisfactory. This study was conducted to analyze how the influence of the financing of the agricultural sector by Islamic banks to increase the exchange rate of farmers in East Java Province ?. In order to answer this question, the data analysis is done using multiple linear regression. The type of data in this study is secondary data with monthly data forms (January 2016 to August 2018). The results of the study indicate that the financing carried out by Islamic Commercial Banks and Sharia Business Units in East Java Province has a significant positive effect on Farmer Exchange Rates. Meanwhile, the financing of the agricultural sector by the Islamic People's Financing Bank does not have a significant effect on the exchange of farmers in East Java Province.